Role of factual evidence and experience on intuition and strategic marketing decision making - Anita, B. (university of Jaffna, 2014)
Corporate world largely relies on empirical evidence for decision making. Decision making is a cognitive process resulting in the choice of a particular course of action from among options available. Strategic marketing decision making has never been easy. Strategic marketing decisions are best taken in a scenario where all or most relevant data is available which is ideal. Most of the times there is lack of information for empirical or factual decision making. It is best then to rely on intuition based decision making. Intuition has also been a key ingredient of decision making for managers in times when most relevant data is available. This research presents strategic marketing decision making based on intuition with some factual evidence versus intuition based on prior knowledge of the market.
Keywords: Cognitive; Decision making; Marketing strategic